2018
DOI: 10.1016/j.yclnex.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Lipids: An insight into the neurodegenerative disorders

Abstract: methods, coupled with the recognition of the role of lipids in many metabolic diseases such as obesity, atherosclerosis, stroke, hypertension and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 120 publications
1
60
0
2
Order By: Relevance
“…These results are consistent with recent studies suggesting that gut microbiome can influence lipid metabolism in various systems (Matey-Hernandez et al, 2018). Moreover, lipid metabolism may play a role in both protection and deterioration of neurons in various neurodegenerative disorders (Dupuis et al, 2008;Shamim et al, 2018).…”
Section: Fatty Acid Metabolism Genes Are Essential For Ha-114-mediatesupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with recent studies suggesting that gut microbiome can influence lipid metabolism in various systems (Matey-Hernandez et al, 2018). Moreover, lipid metabolism may play a role in both protection and deterioration of neurons in various neurodegenerative disorders (Dupuis et al, 2008;Shamim et al, 2018).…”
Section: Fatty Acid Metabolism Genes Are Essential For Ha-114-mediatesupporting
confidence: 93%
“…Over the last few years, many studies have implicated impaired lipid metabolism in various neurodegenerative disorders, including Alzheimer's disease and ALS (Abdel-Khalik et al, 2017;Shamim et al, 2018;Wong et al, 2017). Since our data suggested that HA-114 requires the fatty acid metabolism key component kat-1 and increases acdh-1 expression, we hypothesized that the age-related neurodegeneration models we used might have disrupted lipid equilibrium and that HA-114 might restore lipid content to normal levels.…”
Section: Rhamnosus Ha-114 Restores Lipid Homeostasis In Age-relatementioning
confidence: 95%
“…As an integral component of brain structure, fatty acids play a significant role in healthy brain function. Different diseases/disorders, e.g., Alzheimer's disease, Parkinson's disease, Huntington's disease, schizophrenia, mood disorders, are linked due to altered membrane fatty acid composition and their signalling in disease progression (Bazinet and Layé, 2014; Shamim et al, 2018). The encephalopathy “Reye syndrome” is causally associated with altered fatty acid oxidation (Orlowski, 1999).…”
Section: Dha Deficiency and Human Brain Functionmentioning
confidence: 99%
“…As happens with protein intake; myelination, another essential and required event in neurodevelopment is influenced by a second dietary animal product, lipids. For instance, brain lipids specify the position and role of proteins in the cell membrane and thus control synaptic neuron signals (Shamim et. al.…”
Section: One Of the Evolutionary Consequences Of This Dietary Transitmentioning
confidence: 99%
“…2018). Lipids may also act as transmitters and relay signals to intracellular compartments or other cells from the membrane (Shamim et al, 2018).…”
Section: One Of the Evolutionary Consequences Of This Dietary Transitmentioning
confidence: 99%